Comprehensive school physical activity programs putting research into evidence-based practice - Carson, Russell L. 1975-; Webster, Collin A. 1976- (Shape America, 2020)
"Compendium of research, theories, perspective, and best practices for the latest CSPAP model (with 50+ contributors). It will be a higher ed textbook and a resource for K-12 administrators and teachers"